The Corrosion Resistance of Turbocharger Stator after Plasma Nitriding Process - Pilch, Ondrej; Faltejsek, Petr; Hrubý, Vojtěch; Krbaťa, Michal (Manufacturing Technology Journal, 2017)
The plasma nitriding technology was applied on the turbocharger stator wheel. Martensitic stainless steel X12Cr13 was choosen for the experiment. The influence of plasma nitriding process on the corrosion resistance of selected steel was investigated. The chemical composition of selected steel was verified using the Q4 TASMAN device. After plasma cleaning procedure was plasma nitriding process performed using two stage nitriding procedure. The microstructure and mechanical properties of the nitride layers were studied using optical and laser confocal microscopy and hardness testing. The depths of plasma nitride layers were also estimated using cross-sectional microhardness profiles measuring. The corrosion resistance of plasma nitrided X12Cr13 steel samples were evaluated in a 5 % neutral sodium chloride solution (NSS) in accordance with ISO 9227 standard in the VLM GmbH SAL 400-FL corrosion chamber and visually verified. Microhardness and surface hardness of experimental samples were significantly increased, but the corrosion resistance significantly decreased.
Keywords: plasma nitriding; stainless steel; nitride layer; corrosion resistance